Cambridge IELTS Vol. 4 : Examination Papers from University of Cambridge ESOL Examinations - Published by Cambridge University Press (New York Cambridge University Press, 2005)
This volume contains four authentic IELTS papers from Cambridge ESOL, providing excellent exam practice. An introduction to the different modules is included in each book together with an explanation of the scoring system.
Keywords: English language -- Textbooks for foreign speakers -- English language -- Examinations, questions, etc